2020
DOI: 10.1136/bmjopen-2019-031075
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and prevalence of hepatitis B virus among healthcare workers: a cross-sectional, hospital-based study in Bamenda Health District, NWR, Cameroon

Abstract: Introduction Hepatitis B virus (HBV) is a bloodborne virus which can be transmitted via percutaneous and mucocutaneous exposure to infected body fluid. Healthcare workers (HCWs) who are continuously exposed to different body fluids are at an increased risk of contracting and transmitting this virus. It is thus important to evaluate the knowledge and attitude of HCWs towards HBV and the prevalence of HBV infection among them. Methods This cross-sectional study was carried out between April and September 2017. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 26 publications
7
24
2
3
Order By: Relevance
“…It was also discovered that Lagos residents, fear the cost of HBV/HIV co-infection treatment more than they fear the possibility of death due to the co-infection. This aligns with Akazong, et al [39] who stated that a reason for the negative attitude of some healthcare workers towards HBV patients could be due to the vaccine being costly.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…It was also discovered that Lagos residents, fear the cost of HBV/HIV co-infection treatment more than they fear the possibility of death due to the co-infection. This aligns with Akazong, et al [39] who stated that a reason for the negative attitude of some healthcare workers towards HBV patients could be due to the vaccine being costly.…”
Section: Introductionsupporting
confidence: 85%
“…This is in line with a study done on medicine and health science students in University of Gondar, Ethiopia, which found that about 75% of them have a good attitude towards the treatment and control of HBV; and 82.1% have no issue with treating HBV-positive patients [38]. In another study, it was discovered that 67.8% of healthcare workers in Cameroon have a positive attitude towards HBV-positive patients [39]. On the contrary, a study done on the attitudes of dentists towards patients with these diseases, was found to be negative; with 73% of dentists not being willing to treat patients who are HIV-positive [40].…”
Section: Introductionsupporting
confidence: 81%
“…Stigma and lack of knowledge have been acknowledged as significant barriers to the prevention, diagnosis and treatment of chronic infection [ 25 , 30 , 31 , 32 ]. Negative attitudes toward HBV infection and unwillingness to provide care for CHB patients has been well documented in previous studies among medical students and HCWs in Vietnam, Japan, Iran, Saudi Arabia and other countries [ 10 , 25 , 30 , 31 , 32 , 33 , 34 , 35 ]. These studies also pointed out that students’ attitude is positively correlated with their mean knowledge scores [ 10 , 36 ] and the level of willingness is significantly associated with their confidence in protecting themselves against infection.…”
Section: Discussionmentioning
confidence: 99%
“…This findings of the present study were supported by a study from Ethiopia, which indicating good knowledge but poor practice related to HBV, which resulted in intermediate prevalence of HBV in Ethiopian HCWs [ 38 ]. Another study from Cameroon reported that despite the presence of good knowledge, high prevalence of HBsAg positivity was observed among HCWs [ 39 ]. Thus, it is equally important to have good knowledge as well as follow good medical practices for reducing the burden of viral hepatitis among HCWs.…”
Section: Discussionmentioning
confidence: 99%